Prospective Evaluation of a Multifaceted Intervention to Improve Outcomes in Intensive Care: The Promoting Respect and Ongoing Safety Through Patient Engagement Communication and Technology Study*. Issue 8 (August 2017) - Dykes, Patricia C.; Rozenblum, Ronen; Dalal, Anuj; Massaro, Anthony; Chang, Frank; Clements, Marsha; Collins, Sarah; Donze, Jacques; Fagan, Maureen; Gazarian, Priscilla; Hanna, John; Lehmann, Lisa; et al.
Abstract : Objectives: Studies comprehensively assessing interventions to improve team communication and to engage patients and care partners in ICUs are lacking. This study examines the effectiveness of a patient-centered care and engagement program in the medical ICU. Design: Prospective intervention study. Setting: Medical ICUs at large tertiary care center. Patients: Two thousand one hundred five patient admissions (1, 030 before and 1, 075 during the intervention) from July 2013 to May 2014 and July 2014 to May 2015. Interventions: Structured patient-centered care and engagement training program and web-based technology including ICU safety checklist, tools to develop shared care plan, and messaging platform. Patient and care partner access to online portal to view health information, participate in the care plan, and communicate with providers. Measurements and Main Results: Primary outcome was aggregate adverse event rate. Secondary outcomes included patient and care partner satisfaction, care plan concordance, and resource utilization. We included 2, 105 patient admissions, (1, 030 baseline and 1, 075 during intervention periods). The aggregate rate of adverse events fell 29%, from 59.0 per 1, 000 patient days (95% CI, 51.8–67.2) to 41.9 per 1, 000 patient days (95% CI, 36.3–48.3; p < 0.001), during the intervention period. Satisfaction improved markedly from an overall hospital rating of 71.8 (95% CI, 61.1–82.6) to 93.3 (95% CI, 88.2–98.4; p < 0.001) for patients and from 84.3 (95% CI, 81.3–87.3) to 90.0 (95% CI, 88.1–91.9; p < 0.001) for care partners. No change in care plan concordance or resource utilization. Conclusions: Implementation of a structured team communication and patient engagement program in the ICU was associated with a reduction in adverse events and improved patient and care partner satisfaction. Abstract : Supplemental Digital Content is available in the text.